STUDY OF CONSUMER ACCEPTANCE OF PATIN (Pangasius sp.) FISHBALL WITH THE ADDITION OF SAGO (Metroxylon sp.) FLOUR DIFFERENT CONCENTRATIONS - Yoga Rakasiwi Pratama; Dewita Dewita; Suparmi Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTThis study aimed to determine the effect of the addition of different concentrations of sago flour on the manufacture of patin fishball to determine the best concentration on consumer acceptance. The research method used was a non-factorial Completely Randomized Design (CRD) with 4 levels of treatment, namely, P0 (control), P1(15% sago flour), P2(30% sago flour) and P3 (45% sago flour). The parameter used in this research was organoleptic assessment. The results showed that P1 treatment (15% sago flour) was the best results and was accepted by consumers (85%/68 panelist) with intact appearance characteristics, very attractive with slightly brownish yellow color, dense compact texture and crispy, flavorful, typical fish, delicious, and savory taste.Keywords: Fishball, Flour, Patin, Sago